2018
DOI: 10.1001/jamaneurol.2017.4469
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Neurological Implications of von Hippel–Lindau Disease

Abstract: on Hippel-Lindau (VHL) disease is an autosomal dominant neoplasia syndrome caused by a germline mutation of the VHL tumor suppressor gene (NC_000003.12) located on the short arm of chromosome 3. [1][2][3] This disease carries a prevalence of 1 in 36 000 births 4 and is highly penetrant (>90% penetrance by age 65 years). 3 Patients with VHL disease can develop lesions of the viscera and central nervous system (CNS). Visceral lesions include renal cell carcinomas or cysts, pheochromocytomas, pancreatic neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 70 publications
2
65
1
9
Order By: Relevance
“…According to the American College of Medical Genetics and Genomics standards and guidelines, we found that both variants were pathogenic [16]. According to previous research, there is increasing evidence that CNS HGBs are the most frequent cause of mortality in patients with VHL disease [17,18]. However, some studies reported that approximately 20% of patients have VHL disease resulting from a de novo mutation and have no family history [19].…”
Section: Discussionmentioning
confidence: 78%
“…According to the American College of Medical Genetics and Genomics standards and guidelines, we found that both variants were pathogenic [16]. According to previous research, there is increasing evidence that CNS HGBs are the most frequent cause of mortality in patients with VHL disease [17,18]. However, some studies reported that approximately 20% of patients have VHL disease resulting from a de novo mutation and have no family history [19].…”
Section: Discussionmentioning
confidence: 78%
“…1 Our patient had truncating mutation, correlating to a higher rate of hemangioblastoma, but a lower risk for pheochromocytoma. …”
mentioning
confidence: 67%
“…VHLs is caused by germline mutations of the VHL gene, which is located on chromosome 3 (3p25-26) (11). Mutations in this gene have been reported in all three of its exons and may affect several organs, including the retina, kidneys, adrenal glands, nervous system and pancreas (12,13). Haploinsufficiency of this gene may promote the development of benign cystic lesions, but tumor development depends on allele wild-type inactivation.…”
Section: Discussionmentioning
confidence: 99%